SYNTHESIS OF PHOSPHORAMIDATE DERIVATIVES OF 5-FLUROURACIL AS A POSSIBLE PRODRUGS FOR TARGETING CANCER TISSUE - Mohammad, Mohammad H; Abed, Dhulfiqar Ali (Al-Nahrain Journal of Science, 2010)
5-Fluorouracil (5-FU) is used widely as an anticancer drug to treat solid cancers, such as colon, breast, rectal, and pancreatic cancers; although it s clinical application is limited because 5-FU has gastrointestinal and hematological toxicity. An approach to improve the cancer cell selective properties of 5-fluorouracil is the chemical transformation into reversible derivatives (prodrugs) which are converted to the parent drug by virtue of enzymatic and / or chemical hydrolysis within the cancer tissue. In the present study, three derivatives of 5-fluorouracil has been designed to be synthesized as 5-fluorouracil phosphoramidate prodrugs, compounds (I, II and III) to selectively deliver the 5-fluorouracil into the cancer cells.The generation of the target compounds I, II and III were accomplished following one-pot reaction procedures. The reaction and purity of the products were checked by TLC, the structure of the final compounds was confirmed by their melting points, infra red spectroscopy and elemental microanalysis. The hydrolysis of compounds I, II and III in aqueous buffer solution of pH 6, pH 7.4 and in serum were studied.Compounds I, II and III had acceptable rate of hydrolysis at pH 6 (t = 45.05 min, t = 41.22min and t = 38.80min respectively) and enough stability at pH 7.4 (t = 348.72 min, t = 395.31min and t = 345.38min respectively); and enough stability at serum; therefore these three compounds can selectively deliver 5-fluorouracil into the tumor cells which have pH approximate to (6).According to the results mentioned above, compounds I, II and III can be good candidates as 5-fluorouracil prodrugs that can selectively deliver the parent drug into the cancer cells by the effect of pH and /or enzyme.